Intrastructural help: improving the HIV-1 envelope antibody response induced by virus-like particle vaccines. Issue 3 (May 2017) - Temchura, Vladimir; Überla, Klaus
Abstract : Purpose of review: The importance of IgG Fc-effector functions for the efficacy of HIV vaccines is increasingly recognized. Although different types of vaccines were shown to induce antibodies with different Fc-activities, there is no clear strategy how to raise antibody responses with a desired pattern of Fc-effector functions. Given the central role of T-helper cells in regulating the germinal center reaction and the differentiation of B cells in an antigen-specific manner, the review will discuss whether T-helper cells directed against non-HIV envelope (Env) antigens could be harnessed to improve the HIV-Env antibody response. Recent findings: Comparing CD4 + T-cell responses in HIV-infected individuals with and without neutralizing antibody breadth suggests that robust Gag-specific CD4 + T cells may provide important T-cell help to Env-specific B cells. In a murine model, GagPol-specific T-helper cells were shown to provide intrastructural help for HIV-Env-specific antibody responses after immunization with a virus-like particle vaccine. GagPol-specific T-helper cells imprinted the IgG subtype ratio observed for Gag onto the HIV-Env antibody response and modulated the glycosylation pattern of the HIV Env-specific antibodies. Summary: Intrastructural help is a promising strategy to improve overall levels and Fc-effector functions of the HIV-Env antibody response.